Estrategias de comunicación para fortalecer la imagen institucional de la gobernación de loja - Ruiz Jiménez, María Dolores (2016)
The thesis called "Communication strategies to strengthen the institutional image of the Government of Loja" has established the mechanisms and strategies necessary to establish the name and public agency activity carried out in the province of Loja. The problem was based on How to create new strategies for strengthening the institutional image of the Government of Loja?, established a single line and a permanent balance in the communicational work. Designed for state institution a strategic plan with the aim to improve the process of internal and external communication, for which permanently visited the Governor of the province of Loja, we engage in the work of the communication team we were determining the strengths and weaknesses that exist. The methodology was initially based on the analysis of the problem context. Analytical, qualitative and research and survey and interview: In the development phase of the research work methods were used. The characteristics that we have given to this research have been those of a process with general and local approach in qualitative terms. Thanks to this research and the strategies currently applied more than 70% of Loja citizens know about the work of the Government of Loja. However, we recommend greater presence of the team in the territory, where citizens due to technological limitations, least known of the institution. Keywords: research, plan, strategic communication flow.